KOMUNIKASI PERSUASIF MEMBER TINGKAT “SENIOR BRAND DIRECTOR” MULTI LEVEL MARKETING (MLM) DALAM MEMPERTAHANKAN DOWNLINE BRAND REPRESENTATIVE DI PT. NUSKIN PEKANBARU - Gustiono, Alif; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
PT. Nuskin Pekanbaru is a Multi Level Marketing (MLM) group in which there are a lot of members joined, but the people's perception of the bad MLM makes members who have joined feel hesitant to continue this business, the Senior Brand Director continues to be persuasive to keep members who have joined. The purpose of this research is to find out the persuasive communication used, persuasive communication techniques, the media used to persuade, and to find out what inhibiting factors experienced by Nuskin members in maintaining Downline Brand Representative in Nuskin Pekanbaru.This study used qualitative research methods. The study was conducted at the NUSKIN office, Sudirman business center Jl. Jendral sudirman, Tangkerang selatan, Pekanbaru City. The selection of informants was carried out using a purposive technique. The informants of this research are the Presidential Director at Nuskin Pekanbaru, one Senior Brand Director at Nuskin Pekanbaru, and two Brand Representatives at Nuskin Pekanbaru. The technique of collecting the data are used observation, interview, and documentation. While the validity of the data that researchers use is to extend participation and triangulation.The results showed that, in persuasive communication, the members of the Senior Brand Director used to maintain the Downline Brand representative at Nuskin Pekanbaru were more face-to-face so that they could immediately see the expressions of the Downline that was persuasive. As well as using four techniques namely Putting it up to you technique, Bandwagon technique, Say it with flower technique and Reassurance technique. In addition, members of Nuskin Pekanbaru also use the media namely social media Whatsapp and also the ClickMeeting application. The barriers experienced in persuading Downline Brand Representatives are disturbances based on their nature, namely distance.